The Use of Ontology in Semantic Analysis of the Published Learners Messages for Adaptability - Ait Adda, Samia; Balla, Amar (Swarm Intelligence Based Optimization, 2014)
Communication tools for online learning environments are ways that let learners to exchange messages between them and with their teachers. It is also a way to interpret their social behavior patterns and their learning styles. In this paper, we are interested in the semantic analysis of the contents messages published by learners by use of domain ontology. The purpose of this analysis is to identify the domain concepts that are most published and shared by learners and to keep them into the leaners model as concepts not well mastered. We hypothesize that all concepts edited and exchanged over email, chat and especially in discussion forums can be considered as knowledge poorly or badly acquired by learners and deserve thus more attention and consideration both by the tutor for the pedagogical monitoring of learners on these concepts and from designer of course, to restructure and more enrich the educational content which articulates these concepts identified beforehand in this analysis.